2010
DOI: 10.1073/pnas.0913011107
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene to historic shifts in bald eagle diets on the Channel Islands, California

Abstract: Studies of current interactions among species, their prey, and environmental factors are essential for mitigating immediate threats to population viability, but the true range of behavioral and ecological flexibility can be determined only through research on deeper timescales. Ecological data spanning centuries to millennia provide important contextual information for long-term management strategies, especially for species that now are living in relict populations. Here we use a variety of methods to reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
(35 reference statements)
1
28
0
Order By: Relevance
“…Movement data of reintroduced bald eagles show evidence of dispersal from the CI to the mainland, and in some cases, individuals return to the islands after using inland habitats across western North America (3). Such movements likely took place in the past and may have been more common when CI bald eagle densities were significantly higher than today (2). The dispersal capabilities of bald eagles, higher eagle densities in the past, and greater diversity and abundance of megafauna on the mainland support our explanation.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Movement data of reintroduced bald eagles show evidence of dispersal from the CI to the mainland, and in some cases, individuals return to the islands after using inland habitats across western North America (3). Such movements likely took place in the past and may have been more common when CI bald eagle densities were significantly higher than today (2). The dispersal capabilities of bald eagles, higher eagle densities in the past, and greater diversity and abundance of megafauna on the mainland support our explanation.…”
supporting
confidence: 72%
“…First, they provide an alternative explanation for the terrestrial isotopic signatures of Pleistocene bald eagles from the CI, suggesting that they regularly fed on pygmy mammoth carrion (1). Although this explanation is plausible, it is not more parsimonious than the one that we provided (2). Movement data of reintroduced bald eagles show evidence of dispersal from the CI to the mainland, and in some cases, individuals return to the islands after using inland habitats across western North America (3).…”
mentioning
confidence: 75%
“…It is important to understand how ecosystems function and change through time, and species interactions are an integral part of any ecosystem (61)(62)(63)(64). Some of the carnivore species that were present at RLB are still extant today (e.g., coyotes, gray wolves, mountain lions, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…These methods are not limited to modern systems, and are used to elucidate both large-and small-scale patterns of interaction in mammalian communities with temporal spans ranging from the recent to the Plio-Pleistocene. Reconstructing species interactions in past ecosystems has a rich history [85], and recent investigations have demonstrated that our understanding of the past can facilitate knowledge of modern ecosystems [39,86,126]. Given the scale over which interactions occur, particularly for systems with long-lived organisms, historical and paleontological approaches o↵er windows into nature unavailable to modern ecology.…”
Section: Chapter 6 Synthesismentioning
confidence: 99%